Identification of a temperature-sensitive asparaginyl-transfer ribonucleic acid synthetase mutant of Escherichia coli. - Yamamoto, M (1977)
A temperature-sensitive mutant of Escherichia coli K-12 isolated previously (H. Ohsawa and B. Maruo, J. Bacteriol. 127:1157-1166, 1976) was found to have an alteration in asparaginyl-transfer ribonucleic acid synthetase. This alteration can account for the temperature-sensitive phenotype of the mutant. No evidence was obtained to support the previous suggestion that ribosomal protein S1 is altered in this mutant. Combined with the previous genetic studies, we conclude that the newly defined genetic locus, asnS, for the asparaginyl-transfer ribonucleic acid synthetase maps near pyrD at 21 min on the E. coli chromosome.